Red yeast rice for dyslipidaemias and cardiovascular risk reduction: A position paper of the International Lipid Expert Panel. (September 2022) - Banach, Maciej; Catapano, Alberico L.; Cicero, Arrigo F.G.; Escobar, Carlos; Foger, Bernhard; Katsiki, Niki; Latkovskis, Gustavs; Rakowski, Michal; Reiner, Zeljko; Sahebkar, Amirhossein; Sikand, Geeta; Penson, Peter E.; et al.
Abstract: The risk of atherosclerotic cardiovascular disease (ASCVD) is strongly related to lifetime exposure to low-density lipoprotein (LDL)-cholesterol in longitudinal studies. Lipid-lowering therapy (using statins, ezetimibe and PCSK9 inhibitors) substantially ameliorates the risk and is associated with long-term reduction in cardiovascular (CV) events. The robust evidence supporting these therapies supports their continued (and expanding) role in risk reduction. In addition to these 'conventional' therapeutics, while waiting for other innovative therapies, growing evidence supports the use of a range of 'nutraceuticals' (constituents of food prepared as pharmaceutical formulations) including preparations of red yeast rice (RYR), the product of yeast (Monascus purpureus) grown on rice, which is a constituent of food and is used in traditional Chinese medicine. The major active ingredient, monacolin K, is chemically identical to lovastatin. RYR preparations have been demonstrated to be safe and effective in reducing LDL-C, and CV events. However, surprisingly, RYR has received relatively little attention in international guidelines – and conventional drugs with the strongest evidence for event reduction should always be preferred in clinical practice. Nevertheless, the absence of recommendations relating to RYR may preclude the use of a product which may have clinical utility in particular groups of patients (who may anyway self-prescribe this product), what in the consequence might help to reduce population CV risk. This Position Paper of the International Lipid Expert Panel (ILEP) will use the best available evidence to give advice on the use of red-yeast rice in clinical practice. Graphical Abstract: ga1